Differential patterns of pathology in and interaction between joint tissues in long-term osteoarthritis with different initiating causes: phenotype matters. Issue 7 (July 2020) - Zaki, S.; Smith, M.M.; Smith, S.M.; Little, C.B.
Summary: Objective: To determine if osteoarthritis (OA) progression and joint tissue–pathology associations link specific animal models to different human OA phenotypes. Design: Male 11-week-old C57BL6 mice had unilateral medial-meniscal-destabilization (DMM) or antigen-induced-arthritis (AIA). Joint tissue histopathology was scored day-3 to week-16. Tissue-pathology associations (corrected for time and at week-16) were determined by partial correlation coefficients, and odds ratios (OR) calculated for likelihood of cartilage damage and joint inflammation by ordinal-logistic-regression. Results: Despite distinct temporal patterns of progression, by week-16 joint-wide OA pathology in DMM and AIA was equivalent. Significant pathology associations common to both models included: osteophyte size and maturity ( r > 0.4); subchondral bone (SCB) sclerosis and osteophyte maturity ( r > 0.25); cartilage erosion and chondrocyte hypertrophy/apoptosis ( r > 0.4), SCB sclerosis ( r > 0.26), osteophyte size ( r > 0.3), and maturity ( r > 0.32). DMM-specific associations were between cartilage proteoglycan loss and structural damage ( r = 0.56), osteophyte maturity ( r = 0.49), size ( r = 0.45), and SCB sclerosis ( r = 0.28). AIA-specific associations were between SCB sclerosis and chondrocyte hypertrophy/apoptosis ( r = 0.40) and osteophyte size ( r = 0.37); and synovitis with cartilage structural damage ( r = 0.18). No tissue–pathology associations were common to both models at week-16. Increased likelihood of cartilage structural damage was associated with: chondrocyte hypertrophy/apoptosis (OR>1.7), and osteophyte size (OR>2.3) in both models; SCB sclerosis (OR = 2.0) and proteoglycan loss (OR = 2.4) in DMM; and synovitis (OR = 1.2) in AIA. Joint inflammation was associated positively with cartilage proteoglycan loss (OR = 1.4) and inversely with osteophyte size (OR = 0.21) in AIA only. Conclusion: This study highlights the importance of defining OA-models by initiating mechanisms and progression, not just end-stage joint-tissue pathology.